2010
DOI: 10.1017/s136898001000279x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in food consumption among the Programa Bolsa Família participant families in Brazil

Abstract: Objective: To analyse changes and predictors of change in self-reported food intake among Brazilian families that benefitted from conditional cash transfer (CCT) implemented in the Programa Bolsa Família of the Brazilian Federal Government. Design: A cross-sectional survey. Setting: The study was conducted from September to October 2007 in a nationwide representative household sample of families included in the CCT. Socioeconomic variables, perception of food consumption and food insecurity were evaluated via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 15 publications
2
44
0
10
Order By: Relevance
“…Thus, it is not only the costs that determine the eating choices. De Bem Lignani et al 23 also identified that the higher purchasing power of the population addressed by Brazilian income transfer programs (Bolsa Família) increased the intake of unhealthy foods. Concerning the consumption of beans, POF identified a 30% reduction in the household availability of this item in the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not only the costs that determine the eating choices. De Bem Lignani et al 23 also identified that the higher purchasing power of the population addressed by Brazilian income transfer programs (Bolsa Família) increased the intake of unhealthy foods. Concerning the consumption of beans, POF identified a 30% reduction in the household availability of this item in the same period.…”
Section: Discussionmentioning
confidence: 99%
“…A major concern for low-income persons is a lack of monetary resources. However, increasing monetary resources alone is not sufficient to modify some important consequences of low income and food insecurity, such as obesity (12). Experimental data have suggested that providing monetary vouchers may increase obesity because people have more money to apply to unhealthy food choices (13).…”
Section: Introductionmentioning
confidence: 99%
“…8,27,30 However, methodological problems were identified in other studies which compromised the interpretation of results and weakened the evidence obtained, such as selecting the sample by convenience, small sample size 18,19,25 and not adjusting for confounding variables. 9,16 Evidences obtained in plausibility studies are useful and reliable in evaluating the impact of programs and public policies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the higher the value of the benefit, the higher the intake of all foodgroups. 8 The second study 9 assessed the diets of 747 PBF recipients in a municipality in the South using the Dietary Quality Index (DQI). It was concluded that the majority of recipients' diets were not adequate.…”
Section: Pbf: Family Grant Programmentioning
confidence: 99%